A Self‐Supported High‐Entropy Metallic Glass with a Nanosponge Architecture for Efficient Hydrogen Evolution under Alkaline and Acidic Conditions (Adv. Funct. Mater. 38/2021). (16th September 2021) - Jia, Zhe; Nomoto, Keita; Wang, Qing; Kong, Charlie; Sun, Ligang; Zhang, Lai‐Chang; Liang, Shun‐Xing; Lu, Jian; Kruzic, Jamie J.
Abstract : High‐Entropy Metallic Glass In article number 2101586, Ligang Sun, Jian Lu, Jamie J. Kruzic, and co‐workers develop a high‐entropy metallic glass using a scalable metallurgical technique. Dealloying creates a nanosponge‐like architecture with embedded nanocrystals that provide abundant active sites to achieve outstanding hydrogen evolution activity in a wide pH range. This seminal work will serve as a basis for alloy catalyst design for many years to come.